Biofilm and Materials Science - Kanematsu, Hideyuki; Barry, Dana M. (New York Springer, 2015)
This book explains the formation of biofilm on materials surfaces in an industrial setting. The authors describe new developments in understanding of biofilm formation, detection, and control from the viewpoint of materials science and engineering. The book details the range of issues caused by biofilm formation and the variety of affected industries.
Keywords: Biomedical materials; Bioengineering -- Materials; Microbial ecology; Biomedical engineering; Biomaterials; Microbial Ecology; Biomedical Engineering and Bioengineering